ORGANIZING STRATEGIC MANAGEMENT ACCOUNTING FOR PRODUCTION COSTS IN BUSINESS ENTITIES - Gulmira Khayrullaevna Normatova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines approaches to accounting for costs associated with work in progress in business entities and to organizing their strategic management accounting. It reviews studies by foreign and Uzbek economists in this field and synthesizes their views on the theoretical and methodological aspects of product cost calculation and the organization of strategic management accounting. The article also offers recommendations for improving the strategic management accounting of work-in-progress costs in business entities.